2021
DOI: 10.3390/cancers13112793
|View full text |Cite
|
Sign up to set email alerts
|

Immunotherapeutic Approaches in Malignant Pleural Mesothelioma

Abstract: Malignant pleural mesothelioma (MPM) is a rare and aggressive malignant disease affecting the mesothelium, commonly associated to asbestos exposure. The current therapeutic actions, based on cisplatin/pemetrexed treatment, are limited due to the late stage at which most patients are diagnosed and to the intrinsic chemo-resistance of the tumor. Another relevant point is the absence of approved therapies in the second line setting following progression of MPM after chemotherapy. Considering the poor prognosis of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 148 publications
0
7
0
Order By: Relevance
“…6 7 The broader immunotherapeutic landscape of MPM has been comprehensively reviewed recently. [8][9][10][11][12] The intimate involvement and abundance of leukocytes in MPM 13 from carcinogenesis to diagnosis suggest that the tumor immune microenvironment's (TIME's) composition may influence response to immunotherapy 14 and the tumor's genomic landscape. 15 This review article will focus on cytotoxic T-lymphocyte (CTL) biology and the specific role of TAMs in immunosuppression.…”
Section: Immunity In the Causation And Therapy Of Malignant Pleural Mesothelioma (Mpm)mentioning
confidence: 99%
“…6 7 The broader immunotherapeutic landscape of MPM has been comprehensively reviewed recently. [8][9][10][11][12] The intimate involvement and abundance of leukocytes in MPM 13 from carcinogenesis to diagnosis suggest that the tumor immune microenvironment's (TIME's) composition may influence response to immunotherapy 14 and the tumor's genomic landscape. 15 This review article will focus on cytotoxic T-lymphocyte (CTL) biology and the specific role of TAMs in immunosuppression.…”
Section: Immunity In the Causation And Therapy Of Malignant Pleural Mesothelioma (Mpm)mentioning
confidence: 99%
“…The survival rate for patients with malignant pleural mesothelioma is still low; a population-based study reported average survival times ranging from 5 months to 13.2 months ( 25 ). Although immunotherapeutic approaches to malignant mesothelioma have received much attention, further studies are needed to show a clear advantage over standard chemotherapy ( 26 ). A recent study of immunotherapeutic approach also showed significant and clinically meaningful improvements in overall survival versus standard chemotherapy ( 27 ).…”
Section: Discussionmentioning
confidence: 99%
“…A better treatment is urgently needed. Biological targeted therapy for MPM is not recommended because of the lack of known oncogenic driver alterations (7). Clinical studies of MPM immunotherapy has underwent a transition from relapse to second-line, monotherapy to combination, and now seemed promising in some phase II clinical studies (8).…”
Section: Introductionmentioning
confidence: 99%